Perancangan Program Pembayaran Administrasi Sekolah Berbasis Website Menggunakan Metode Waterfall - Hasan Muhamad; Ahmad Hafidzul Kahfi; Agung Fazriansyah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Payment of school administration fees is still problematic, including manual data collection and processing of payment information. Recorded reports still use ledgers, making work less efficient, and a lot of time and energy is wasted searching for student data and archiving it by committee staff. In the current technological era, there is a need to renew the use of technology in education to help manage school finances so that data collection and processing of payment information becomes effective and efficient. This study describes the design of a website-based school administration payment program. This design is intended to assist committee staff in recording school administration payments. The research method used is the waterfall-type software development method. In database design using Entity Relationship Diagram and Logical Record Structure, while for making applications using the PHP programming language. With this program, the administrative payment process is better, easier, and faster